ChemInform Abstract: Concise Stereoselective Total Synthesis of (+)‐Mueggelone. Issue 29 (1st July 2013) - Kumar, Dachepally Aravind; Meshram, Harshadas Mitaram
Abstract (+)‐Mueggelone (I) is synthesized from commercially available and inexpensive starting materials via Sharpless epoxidation, Jacobsen resolution, lactonization and cross metathesis.